Activation of the Entrepreneurial Potential in the Teaching process - Stašāne, Janīna; Voronovs, Viktors (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
At the present stage of the development of the modern society entrepreneurship is being positioned as an effective form of implementing human potential. One of the main factors in the management process is entrepreneurial abilities, which form the potential to be used in the management activity. In order to rebuild the economy and gain a higher level of employment, Europe needs more entrepreneurs. Evaluating the role of education in the development of entrepreneurship, the issue of the influence of teaching curriculum on the development of entrepreneurial potential has become topical and widely-discussed. The article clarifies what entrepreneurial skills are to be developed in order to start and deal with entrepreneurship and how higher education contribute to acquisition of such skills. The aim of the article is to define how teaching curriculum contribute to the development of entrepreneurial potential. The research methods: monographic, abstract logical, graphical method, questionnaire.